Design and application of batch tilting of plates to multiple angles using kirigami hinges - Taiki SUGIHARA; Satoshi IKEZAWA; Eiji IWASE (Mechanical Engineering Journal)
We developed a design to achieve the simultaneous tilting of structures to multiple angles by stretching. We focused on the tilting of plates using a kirigami hinge structure and proposed a method of connecting hinges with varying stiffness in series. To characterize the deformation of the kirigami hinge structure, we fabricated test pieces with varying cut line widths, hinge lengths, and beam widths and measured the relationship between load and tilt angle. The experimental results demonstrate that the tilting characteristics of a kirigami hinge structure under load vary with its geometric parameters. On the basis of experimental results, we fabricated a mechanism to simultaneously tilt nine flat plates to three different angles by varying the cut line width. Additionally, we fabricated a kirigami-hinged mirror array for an autostereoscopic display, which achieves a parallax effect by arranging two sets of mirrors with distinct tilt angles.